The recovery stress of hot drawn and annealed NiTiNb SMA considering effect of temperature and cyclic loads: Experimental and comparative study. (1st February 2022) - Pan, Shengshan; Zou, Cunyu; Zhang, Xue; Yan, Dong; Chen, Yuanmeng; Hui, Huaxing
Abstract: Shape memory alloy (SMA) has good memory effect and hyperelasticity, which can be applied in civil engineering for seismic shock absorption and active strengthening. The Nickel-titanium-niobium (NiTiNb) SMA is widely adopted as reinforcement to increase the capacity of bridge piers and/or girders. However, the NiTiNb SMA is inconvenient to apply for two reasons. First, the NiTiNb SMA is generally processed by annealing the row wires at a high temperature (850℃ ± 10℃), meaning that a lot of energy is required. Second, the annealed SMA usually needs to be pre-tensed at a low temperature (about −60℃) to obtain a sufficient recovery stress, which requires a specific device and environment. Comparatively, the NiTiNb SMA treated with hot drawn process doesn't require high temperature in the fabrication, thus consumes less energy. Meanwhile, the hot drawn SMA can be pre-tensed at room temperature to obtain an adequate recovery stress (around 700 MPa), which overcomes the inconvenience of the annealed SMA. So far, however, the mechanical properties of the hot drawn SMA have not been fully studied, which limits its practical application. In this study, therefore, the mechanical properties of hot drawn NiTiNb SMA wires were investigated through the monotonic tension, thermal excitation and cyclic loading tests. The mechanical properties of the hot drawn SMA were compared with those of the annealed ones. The results showed that, under the monotonic loading, the yield and ultimate strength of the hot drawn SMA is greater than the annealed one by 12.7% and 43.0%. Compared to the annealed SMA, the maximum and remained recovery stress of the hot drawn SMA increases by 70.5% and 18.2%, respectively. Moreover, the hot drawn SMA is better than the annealed SMA in resisting the degradation of effective stress under the incremental cycle amplitude test.